Use of the constant volume combustion chamber to examine the properties of autoignition and derived cetane number of mixtures of diesel fuel and ethanol. (15th July 2017) - Kuszewski, Hubert; Jaworski, Artur; Ustrzycki, Adam; Lejda, Kazimierz; Balawender, Krzysztof; Woś, Paweł
Highlights: Ignition and combustion delay for some diesel-ethanol mixtures were measured. Tests of autoignition properties were conducted for different injection pressures. Derived cetane number (DCN) for ethanol-diesel mixtures is discussed. Abstract: Due to increasing fuel consumption in various industries, especially in road transport, interest in increasing the market proportion of renewable fuels is growing. One of such fuels is ethanol. The raw materials for production of ethanol may include sugar beets, sugar cane, potatoes and many other plants containing starch. Ethanol can be used as a self-contained fuel in positive-ignition engines, which undergo relatively minor technical modifications. However, in diesel engines with compression ignitions, due to, e.g., a very low cetane number, this fuel cannot be used. Therefore, more attention is given to fuels consisting of mixtures of diesel fuel with certain proportions of ethanol. In this paper, the properties of autoignition mixtures of conventional diesel and ethanol, with ethanol content of up to 14% (v/v), were examined. A combustion chamber of constant volume was used in the study. The effect of injection pressure in the range of 80 MPa–140 MPa on the period of ignition delay and the period of combustion delay was determined in the study. In addition, for each mixture of diesel fuel and ethanol, the value of derived cetane number was examined. The studies have shown that with increasing proportions of ethanol, the ignition and combustion delays periods increase and the increase in fuel injection pressure in varying degrees shortens those periods. It was also shown that in the range of 14% ethanol, for every 2% increase in the proportion of ethanol, the derived cetane number of the mixture of diesel and ethanol is reduced by an average of 1.7 units.